Considering Tangible Benefit for Interdependent Donors: Extending a Risk–Benefit Framework in Donor Selection. Issue 10 (17th May 2017) - Van Pilsum Rasmussen, S. E.; Henderson, M. L.; Kahn, J.; Segev, D. L.
Abstract : From its infancy, live donor transplantation has operated within a framework of acceptable risk to donors. Such a framework presumes that risks of living donation are experienced by the donor while all benefits are realized by the recipient, creating an inequitable distribution that demands minimization of donor risk. We suggest that this risk‐tolerance framework ignores tangible benefits to the donor. A previously proposed framework more fully considers potential benefits to the donor and argues that risks and benefits must be balanced. We expand on this approach, and posit that donors sharing a household with and/or caring for a potential transplant patient may realize tangible benefits that are absent in a more distantly related donation (e.g. cousin, nondirected). We term these donors, whose well‐being is closely tied to their recipient, "interdependent donors." A flexible risk–benefit model that combines risk assessment with benefits to interdependent donors will contribute to donor evaluation and selection that more accurately reflects what is at stake for donors. In so doing, a risk–benefit framework may allow some donors to accept greater risk in donation decisions. Abstract : This viewpoint explores the consideration of the donor–recipient relationship and potential tangible benefits in live donor evaluation, suggesting that an expanded framework of risk–benefit balance may allow some donors to accept greater risk in donation decisions.